Customers’ Choice Criteria of Shopping Malls: An Exploratory Study of Choice Criteria in Shopping Mall Selection - Yap, Ko Shin (2010)
This is a research on customers‟ choice criteria on shopping malls. The result of the analysis of the interviews with the 30 respondents has indicated that Malaysians choice criteria on shopping malls is not dissimilar with the results of earlier researches conducted in the developed economies. The identification of the critical attributes of shopping malls will be useful to serve as a guide for mall management to upgrade their current mall standards and service to compete effectively for customers and for mall developers who intend to develop new malls in the country. The attributes identified have been listed clearly and concisely and which are not difficult to be included in the plans for upgrade or development. The analysis of the research is consistent with findings of earlier works in most of the important areas. The research confirmed that Malaysians behave in similar patterns with people living in other parts of the world when it comes to choosing which shopping malls to visit for shopping, meeting friends or other leisure activities. The mall which can attract more customers will make more profits for all the stakeholders, be it the mall developers, the mall management, the mall tenants, the suppliers and creditors and all the staff working in the mall, either as maintenance or service personnel. Users of this research paper should be aware of the limitations governing this research. The size and demographics of the sample in terms of racial composition, range of earnings bands, age groups, genders and the concentration within the Klang Valley may predispose the accuracy of the findings and ultimately the analysis and the conclusions drawn. However, it must be pointed out that the findings are in line with earlier researches done in other parts of the world especially in the developed countries. It is hoped that future researches on this subject will strife to overcome the shortcomings that have been identified in this research.